Opening the black box: Toward a field systems approach to the study of teaching in adult education - John M. Dirkx; Wayne A. Babchuk; Tom L. Sharpie (Adult Education Research Conference, 1995)
This paper reports the development and implementation of a contextually driven research methodology for studying the process of teaching within adult education settings. The significance and theoretical basis for this approach, as well as a detailed description of the analytic system and its potential applications for research and practice are discussed.